Engineered microparticles and nanoparticles for fibrinolysis - Disharoon, Dante; Marr, David W. M.; Neeves, Keith B. (Journal of thrombosis and haemostasis, 2019)
Fibrinolytic agents including plasmin and plasminogen activators improve outcomes in acute ischemic stroke and thrombosis by recanalizing occluded vessels. In the decades since their introduction into clinical practice, several limitations of have been identified in terms of both efficacy and bleeding risk associated with these agents. Engineered nanoparticles and microparticles address some of these limitations by improving circulation time, reducing inhibition and degradation in circulation, accelerating recanalization, improving targeting to thrombotic occlusions, and reducing off‐target effects; however, many particle‐based approaches have only been used in preclinical studies to date. This review covers four advances in coupling fibrinolytic agents with engineered particles: (a) modifications of plasminogen activators with macromolecules, (b) encapsulation of plasminogen activators and plasmin in polymer and liposomal particles, (c) triggered release of encapsulated fibrinolytic agents and mechanical disruption of clots with ultrasound, and (d) enhancing targeting with magnetic particles and magnetic fields. Technical challenges for the translation of these approaches to the clinic are discussed.